Filed education and youth: problematizations from the idea of conflict - Rafael Rossi; Maria Peregrina de Fatima Rotta Furlanetti; Cleiton Aparecido Ferraz; Elen Rosana Ferrato (Universidade Federal de Santa Maria, 2014)
Through this paper we question the need for discussion of the agrarian question conflictualities with the youth field. This need is justified because of two arguments: the continuous recognition and collective union and educational principle in mobilization and peasant resistance and also the act permanent researcher in knowing the peasant reality in an effort to promote the effective field of educational research. Therefore, we need to understand the concept of conflict and field education as a practice intrinsic to educational research in the field.